Evaluation of airflow characteristics before and after septoplasty in unilateral cleft patients with a deviated nasal septum: a computational fluid dynamics study. Issue 4 (April 2021) - Ramanathan, M.; Ramesh, P.; Aggarwal, N.; Parameswaran, A.; Sailer, H.F.; George, A.E.
Abstract: The aim of this study was to evaluate changes in airflow characteristics before and after septoplasty in unilateral cleft lip and palate (UCLP) patients using computational fluid dynamics (CFD) models. The study was designed as a prospective cohort study involving pre- and postoperative computed tomography data from 12 UCLP patients with a deviated nasal septum who underwent septoplasty. CFD analysis of nasal airflow was conducted to study changes in velocity, pressure, volume, nasal resistance, and wall shear stress of the nasal domain before and after surgery. The study results demonstrated a statistically significant difference in pressure drop after septoplasty: median 116.10 Pa (interquartile range (IQR) 749.02 Pa) preoperative compared with 43.39 Pa (IQR 349.01 Pa) postoperative ( P  =  0.004). Maximum wall shear stress was found to be approximately three times lower after septoplasty: median 6.15 Pa (IQR 1908.62 Pa) preoperative versus median 2.51 Pa (IQR 540.06 Pa) postoperative ( P  = 0.002). Changes in nasal resistance were also found to be statistically significant: median 460.59 Pa·s/l (IQR 1946.99 Pa·s/l) preoperative versus median 166.61 Pa·s/l (IQR 694.08 Pa·s/l) postoperative ( P  = 0.04). These values demonstrate significant changes in flow dynamics after surgery indicative of a more uniform airflow pattern and stabilization of the nasal mucosa.